2018
DOI: 10.1038/s41398-018-0204-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the genetic architecture of general and specific psychopathology in adolescence

Abstract: Whilst associations between polygenic risk scores (PRSs) for schizophrenia and various phenotypic outcomes have been reported, an understanding of developmental pathways can only be gained by modelling comorbidity across psychopathology. We examine how genetic risk for schizophrenia relates to adolescent psychosis-related and internalizing psychopathology using a latent modelling approach, and compare this to genetic risk for other psychiatric disorders, to gain a more comprehensive understanding of the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 64 publications
7
53
1
Order By: Relevance
“…Regarding the lack of association between exposure to bullying and previously associated personality traits, 15,41 the PGSs used in this study were based on large studies (eg, based on GWAS samples >450 000 for irritability and >160 000 for neuroticism). Considering that such PGSs have been reported to contribute to child outcomes, 42 the lack of association unlikely reflects insufficient power. Instead, our findings suggest that some of the previously observed associations might be driven by co-occurring internalizing or externalizing symptoms.…”
Section: Research Original Investigationmentioning
confidence: 99%
“…Regarding the lack of association between exposure to bullying and previously associated personality traits, 15,41 the PGSs used in this study were based on large studies (eg, based on GWAS samples >450 000 for irritability and >160 000 for neuroticism). Considering that such PGSs have been reported to contribute to child outcomes, 42 the lack of association unlikely reflects insufficient power. Instead, our findings suggest that some of the previously observed associations might be driven by co-occurring internalizing or externalizing symptoms.…”
Section: Research Original Investigationmentioning
confidence: 99%
“…Several studies have used polygenic scores for schizophrenia, ADHD and other psychiatric disorders to predict general psychopathology in childhood. An increasing amount of evidence converges on the finding that few polygenic effects specific to individual aspects of psychopathology remains after conditioning on the p factor (Brikell et al., ; Jones et al., , ; Riglin et al., ). These studies also suggest that genetic risk for psychiatric disorders emerges in childhood, in the form of continuously measured behaviour problems.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there was an initial assumption that psychotic experiences in adolescence would specifically increase the risk for schizophrenia, evidence suggests a nonspecific increased risk for a broader psychopathology 10 , suggesting that research on psychotic experiences may have an important role in understanding the pathway to a wide array of clinical diagnoses 5 . However, to date no study has found strong evidence for association between genetic liabilities for schizophrenia or any other mental disorder with psychotic experiences 7,8,[11][12][13] .…”
Section: Introductionmentioning
confidence: 99%